A Systematic Analysis on Blockchain Integration With Healthcare Domain: Scope and Challenges - Sabita Khatri; Fahad Ahmed Alzahrani; Md Tarique Jamal Ansari; Alka Agrawal; Rajeev Kumar; Raees Ahmad Khan (IEEE Access, 2021)
A secure, smart and peer-to-peer transactions framework can be developed by Blockchain. Blockchain has enormous potential to turn health care systems as a horizontal technology, which has changed many fields of industry. The aim of this article is to critically review 50 papers published between 2015 and 2020 on blockchain-based health systems. 36 of these were journal papers; 7 were from conferences, 4 were from various symposiums; 3 were from seminars and 1 chapter was written in the book. Three key questions will be answered in this report. Firstly, what are the emerging trends of blockchain application development in healthcare from a technical perspective? Secondly, in what ways will the systematic analysis presented here contribute to a better understanding of the potential for incorporating blockchain-based technologies into the healthcare domain? Third, what are the important challenges in adopting blockchain as a solution in the healthcare domain? The descriptive analysis contains in this article shows the statistical statistics on the strategies of these 50 papers reveal that many of the blockchain systems proposed are using privately held blockchain and Ethereum platforms. We also address possible emerging trends of blockchain application such as blockchain integration with artificial intelligence, cloud based solutions and parallel block chain architecture.